2018
DOI: 10.30773/pi.2017.05.31.1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences of Occupational Stress Associated with Suicidal Ideation among South Korean Employees: The Kangbuk Samsung Health Study

Abstract: ObjectiveIn this study, the relationship between occupational stress and suicidal ideation was investigated, focusing on gender differences among Korean employees.MethodsCross-sectional data for 53,969 workers were collected at Kangbuk Samsung Hospital health screening centers. Risk of suicidal ideation was assessed using a self-reported questionnaire examining suicidal ideation during the past year. Occupational stress was measured using 24 items of the Korean Occupational Stress Scale-Short Form (KOSS-SF). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…The prevalence of suicidal ideation showed a wide range in the general population or the medical personnel. However, medical professionals hold a higher rate of 12-month and lifetime suicidal ideation than the general population ( Kim et al., 2018 ; Han et al., 2016 ; Cao et al., 2015 ; Cano-Langreo et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of suicidal ideation showed a wide range in the general population or the medical personnel. However, medical professionals hold a higher rate of 12-month and lifetime suicidal ideation than the general population ( Kim et al., 2018 ; Han et al., 2016 ; Cao et al., 2015 ; Cano-Langreo et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have reported an association between educational level and suicide risk [ 32 ]. There is also evidence that working-related factors may be related to suicide outcomes [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In model 3, general characteristics (age, BMI, smoking, alcohol consumption, regular exercise), occupational characteristics (shift work, job tenure), chronic diseases, and CES-D were adjusted by entering covariates. Sex differences have been found in the relation between job stress and suicidal ideation [ 23 24 25 26 ]. Therefore, in all our regression models, all data were stratified by sex.…”
Section: Methodsmentioning
confidence: 99%